Design and analysis of an ultrawide-band distributed CMOS mixer. - Safarian, A.Q (IEEE Transactions on VLSI systems)
This paper presents the design and analysis of a novel distributed CMOS mixer for ultrawide-band (UWB) receivers. To achieve the UWB RF frequency range required for the UWB communications, the proposed mixer incorporates artificial inductance-capacitance (LC) delay lines in radio frequency (RF), local oscillator (LO), and intermediate frequency signal paths, and single-balanced mixer cells that are distributed along these LC circuits. Closed-form analytical model for the conversion gain of the mixer is presented. Furthermore, a comprehensive noise analysis of the proposed distributed mixer is carried out, which includes calculation of the mixer noise figure (NF) and derivation of the optimum number of stages, n, minimizing the NF. The designed mixer is capable of covering the RF and LO frequencies over a wide range of frequencies from 3.1-8.72 GHz. A two-stage distributed mixer has been fabricated in a 0.18-μm CMOS process. Experiments show a conversion gain of more than 2.5 dB for the entire range of the frequencies. The dc power consumption is 10.4 mW.